Brand personality from an Islamic perspective: a conceptual analysis of Aaker’s model - Ahmed, Muhammad; Jan, Muhammad Tahir; Hassan, Arif (IIUM Press, International Islamic University Malaysia, 2018)
Current challenges reflect intense competition in the market and low switching cost of customers. For any brand to be appealing and ultimately profitable, it necessitates differentiation in comparison with other brands. Marketers engage in various differentiation techniques such as Aaker’s brand personality model. Aaker’s model contains five dimensions (sincerity, excitement, competence, sophistication, and ruggedness) along with 42 underlying aspects. Brand personality helps in developing customer-brand relationship, brand image, and brand commitment. Extensive research has been done based on the above model yet several scholars have criticised it based on issues such as generalizability across countries and cultures. Religion being an important part of culture has also been ignored in the brand personality domain. This research proposes an Islamic brand personality model, which not only looks into the dimensions, but also examines the underlying aspects based on the Qur’an, hadith and the scholarly work of both traditional and modern Muslim scholars. This paper found that the Islamic brand personality model contains two new dimensions, namely trustworthiness and justice in addition to the existing dimensions. This model can benefit any Islamic brand (Islamic bank, Islamic Insurance company etc.) to differentiate itself from others, especially from conventional brands in order to develop a potentially larger Muslim consumer market.